Bolivia's Net Zero path: Investment needs, challenges, and opportunities - Andersen, Lykke E.; Gonzales, Luis E.; Malky, Alfonso (Frontiers in Climate, 2022)
Due to high levels of deforestation, Bolivia's per capita CO2 emissions are currently among the highest in the world. Indeed, at more than 25 tCO2eq/person/year, they far exceed the per capita emissions of the United States and the United Arab Emirates. Achieving Net Zero would require a complete change of the current resource-intensive development model and would especially have to adjust the incentives that are promoting the rapid expansion of soybean farming and cattle ranching in the Bolivian Amazon and Chiquitano forests. This paper identifies the main sources of emissions in Bolivia and the most cost-effective measures to reduce them, under the condition that the selected measures do not decrease average incomes nor increase poverty compared to the Business-as-Usual scenario. The paper estimates the magnitude of the investment needed to reduce net emissions to zero by 2050 at about 150 billion or 7.8% of Bolivia's GDP between 2022 and 2050. To make sure that poor people are not hurt by the Net Zero strategy, most of the funds should be used to promote alternative and more sustainable economic opportunities for Bolivians, including resilient and diverse agro-forestry activities, zero-deforestation beef production, nature-based tourism, high value-added wood products, scientific research, etc. These alternative opportunities should include women as much as possible, so as to provide more gender equal opportunities than the traditional activities at the agricultural frontier. The paper reviews different financing options and proposes a simple, easily verifiable, performance-based mechanism, that shares the costs and benefits of reduced deforestation fairly. Finally, the paper discusses the main social, economic, and political challenges to achieving these goals.